Electrochemical and electronic structure properties of high-performance supercapacitor based on Nd-doped ZnO nanoparticles. (March 2023) - Sahu, J.; Kumar, Shalendra; Ahmed, Faheem; Alvi, P.A.; Dalela, B.; Phase, D.M.; Gupta, M.; Dalela, S.
Abstract: Recently, hybrid supercapacitors gained the interest of energy experts because of their high energy/power density and long lifespan. In this manuscript, Zn1-x Ndx O (x = 0.00, 0.01, 0.03, and 0.05) nanoparticles were synthesised using the microwave assisted co-precipitation method and characterized using XRD, Raman, TEM, XAS, and electrochemical analyses.The HR-TEM images confirmed that all of the samples exhibited spherical morphologies with average particle sizes in the range of 17–20 nm. The XRD and Raman spectroscopy studies infer that crystallinity enhances with increase in the doping concentration. The Nd ions were revealed to possess a valence state of +3, while the Zn ions had a valence state of +2, confirmed from XAS analyses. The electrochemical analysis showed that 3 % Nd-doped ZnO electrode exhibited the maximum specific capacitance (SC) of 154 F/g, at a current density of 2.5 A/g and the best cycle stability when compared to the undoped and other Zn1-x Ndx O samples (retaining 92 % after 1000 cycles). The specific capacitance of undoped ZnO determined at a current density of 2.5 A/g was found to be 21 F/g. The energy density and specific power of a 3 % Nd 3+ -doped ZnO supercapacitor were measured at 7.36 Wh/kg and 730 W/kg, respectively. The electrochemical results suggest that Nd 3+ -doped ZnO material would serve as an electrode material for supercapacitors application. Graphical abstract: Synthesis using microwave co-precipitation method and the formation of electrode (Left diagram), Nyquist plots withinset shows Nyquist plot zoom-in at high frequency along with equivalent circuit for undoped ZnO and NZO nanoparticles (Right top diagram) and Cyclic performance of N3ZO electrode for 1000 cycles at a JD of 2.5 A/g (Right bottam diagram). Unlabelled Image Highlights: Zn1-x Ndx O nanoparticles synthesized using co-precipitation route. XAS spectra report electronic structure with 3+ oxidation state of Nd cation. Zn0.97 Nd0.03 O electrode had highest specific capacitance of 154 F/g at 2.5 A/g. Best cycle stability (retaining at 92% after 1000 cycles). Energy density and specific power of Zn0.97 Nd0.03 O supercapacitor were 7.36 Wh/kg and 730 W/kg.